2014
DOI: 10.11622/smedj.2013235
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal glomerulonephritis in a healthy child: a case report and literature review

Abstract: following respiratory symptoms, have rarely been described. (1,2) Herein, we present a previously healthy child who developed pneumococcal AGN following submandibular and cervical lymphadenitis complicated with respiratory problems, and in whom AGN was confirmed on blood culture. We also review the relevant literature. CA S E R E PO RTA previously healthy four-year-old boy presented to Hospital Kuala Lumpur, Malaysia, with a one-week history of fever and neck swelling. Two days prior to admission, he developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…In most PIGNs associated with pneumococcal infection in children, nephritis develops within 1 week after fever onset, [2][3][4][5][7][8][9] whereas it develops within 1-2 weeks in PSGN cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most PIGNs associated with pneumococcal infection in children, nephritis develops within 1 week after fever onset, [2][3][4][5][7][8][9] whereas it develops within 1-2 weeks in PSGN cases.…”
Section: Discussionmentioning
confidence: 99%
“…1) PIGN caused by other pathogens, including Streptococcus pneumoniae, has been reported occasionally. [2][3][4][5][6][7][8][9] In this study, we report a case of PIGN associated with S. pneumoniae and influenza A virus infection in a 6-year-old Korean child and review the cases reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The most commonly related agents are S. pneumoniae and M. pneumoniae , but other bacteria, virus and parasites have also been described. 1-5 The serotypes of S. pneumoniae described as nephritogenic are 5, 6B, 7, 9, 14, 15, and 17F. 1-5…”
Section: Discussionmentioning
confidence: 99%
“…Haematu- ria, proteinuria, and elevated blood pressure indicated the development of nephritic syndrome in our patient. Cases of adults and children developing a clinically apparent pneumococcal disease and subsequently acute glomerulonephritis, have been previously described [39][40][41][42] . Streptococcus pneumoniae is now a recognized cause of postinfectious glomerulonephritis (PIGN).…”
Section: Discussionmentioning
confidence: 99%